Candidate Genes Associated With Neurological Findings in a Patient With Trisomy 4p16.3 and Monosomy 5p15.2 - Corrêa, Thiago; Poswar, Fabiano; Feltes, Bruno César; Riegel, Mariluce (Frontiers in Genetics, 2020)
In this report, we present a patient with brain alterations and dysmorphic features associated with chromosome duplication seen in Wolf-Hirschhorn syndrome (WHS), and chromosomal deletions in a critical region responsible for Cri-du-chat Syndrome (CdCS). Chromosomal Microarray Analysis (CMA) revealed a 41.1 Mb duplication encompassing the band region, 4p16.3-p13, and a 14.7 Mb deletion located between the bands, 5p15.33-p15.1. The patient’s clinical findings overlap with previously reported cases of chromosome 4p duplication syndrome and CdCS. The patient’s symptoms are notably similar to those of CdCS patients as she presented with a weak, high-pitched voice, and showed a similar pathogenicity observed in the brain MRI. These contiguous gene syndromes present with distinct clinical manifestations. However, the phenotypic and cytogenetic variability in affected individuals, such as the low frequency and the large genomic regions that can be altered, make it challenging to identify candidate genes that contribute to the pathogenesis of these syndromes. Therefore, system biological and CMA techniques were used to investigate the extent of chromosome rearrangement on critical regions in our patient's phenotype. We identified the candidate genes PPARGC1A, CTBP1, TRIO, TERT, and CCT5 that are associated with the neuropsychomotor delay, microcephaly, and neurological alterations found in our patient. Through investigating pathways that associate with essential nodes in the protein interaction network, we discovered proteins involved in cellular differentiation and proliferation, as well as proteins involved in the formation and disposition of the cytoskeleton. The combination of our cytogenomic and bioinformatic analysis provided these possible explanations for the unique clinical phenotype, which has not yet been described in scientific literature.